2021
DOI: 10.20417/nzjecol.45.5
|View full text |Cite
|
Sign up to set email alerts
|

Rivers as obstacles to home range expansion by the brushtail possum

Abstract: Strategies for defending large tracts of land from mammalian pest incursion are urgently needed. We report on a study investigating whether brushtail possum (Trichosurus vulpecula) range expansion into a controlled area was restricted by a watercourse. The true left of the Orongorongo River valley was treated with 1080 poison baits, and a 250 ha area bordering the river on the true right was excluded from treatment. Nontoxic cereal bait containing pyranine biomarker was sown repeatedly over half of the exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is likely that most, if not all, of the animals detected after TA#2 were resident survivors. Small-scale field trials suggest that rivers may be an obstacle at least to immediate reinvasion by most possums and rats, particularly in non-dispersal periods (Cook et al 2021;ZIP 2019b). In contrast, rats detected on cameras after the dual 1080 field trial in Nugent et al (2019) were found at the edges of the treatment blocks (no natural barriers), on a similar timeline (4-6 weeks), and assumed to be re-invaders.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that most, if not all, of the animals detected after TA#2 were resident survivors. Small-scale field trials suggest that rivers may be an obstacle at least to immediate reinvasion by most possums and rats, particularly in non-dispersal periods (Cook et al 2021;ZIP 2019b). In contrast, rats detected on cameras after the dual 1080 field trial in Nugent et al (2019) were found at the edges of the treatment blocks (no natural barriers), on a similar timeline (4-6 weeks), and assumed to be re-invaders.…”
Section: Discussionmentioning
confidence: 99%
“…Possum reinvasion can be reduced by selecting sites that utilise natural barriers to movement, such as alpine ranges and cold, fast rivers [ 30 , 34 , 35 ]. Here, we present a case study illustrating this approach to possum elimination at the >11,000 ha scale in the Perth River Valley, South Westland, New Zealand, focusing on detection and removal.…”
Section: Introductionmentioning
confidence: 99%
“…The remove and protect strategy is best served by treating large areas, ideally in the tens of thousands of hectares. This reduces reinvasion pressure by shrinking the boundary-to-treatment-area ratio and improving the flexibility to use natural barriers to movement [14,15].…”
Section: Introductionmentioning
confidence: 99%